The Inventory of Native, Introduced and Invasive Vegetation in Tree-Pole Regeneration in Laweyan Village, Surakarta - Kinanthi, Asih; Nida Farikha, Khotrotun (Universitas Veteran Bangun Nusantara, 2023)
The existence of invasive foreign plants is a threat to the global ecosystem. Its rapid growth often causes this plant to destroy the original habitat in an area. This research aims to identify tree-pole regeneration species in Laweyan Village. This research was carried out by direct observation using a sampling method with a plot measuring 10 x 10 meters and analyzed descriptively. Based on the results of research conducted in Laweyan Village, it was found that there were 38 species of pole and tree regeneration vegetation which were divided into 3 types based on their origin, namely native, introduced and invasive species. There were 19 species of native plants, 15 species of introduced plants, and 4 species of invasive plants. Meanwhile, based on their function, plants are divided into three, namely fruit plants, shade plants and ornamental plants. The plants that dominate based on their function are fruit plants, totaling 16 types.